(untitled) (Medico Legal Update, 2021)
Introduction: Internet usage has become a big part of many people’s lives, and among the many uses Social Networking Sites (SNS) which became very prevalent. How privacy concerns, trust and control are affecting SNS usage and self-disclosure has become an important question for many people. Aim: Aim of the study is to assess the information disclosure and control on online social network sites among medical undergraduates. Methodology: The study was conducted at Saveetha medical college and hospital among medical undergraduates. A questionnaire on usage of online social networks and information disclosures was administered and analysed it for reliability, social network site usage, privacy concerns, and disclosure of autobiographical memories. Result: Almost 81.1% of the people feel that their browsing history were tracked by social networking sites. Instagram is mainly used app by medical undergraduates (40%). Conclusion: There is an excess usage of social networking sites and easy information disclosure is seen in the population.